Baroque in the Byzantine Literature: Theodore Prodromos (Circe de clásicos y modernos, 2025)
It is laid out the possibility of finding, in the ‘Renaissance’ of twelfth century and in particular in Theodore Prodromos, some baroque characteristics of his works, specially in his satires and mimes. I is stressed the presence of baroque themes (be-seem, reality-illusion, ruse-veracity, spirit of world, misery, old age, hideousness, etc.) and typic stylistic use of hyperbole, pathos, grandiloquence. It is linked this presence and employment to personal situations of the author and to the context of his time; and it is maintained that they represent baroque theme and style in the middle of a classical conception of the literature.
Keywords: Baroque; Byzance; Theodore Prodromos; satire; mime